Use of Imaging in Cutaneous Squamous Cell Carcinoma to Detect High-Risk Tumor Features, Nodal Metastasis, and Distant Metastasis: A Systematic Review - Libson, Karissa; Sheridan, Connor; Carr, David R; Shahwan, Kathryn T (Dermatologic surgery, 2024)
Imaging has been shown to impact management and disease outcomes in cutaneous squamous cell carcinoma, but the literature on optimal modalities is lacking. To perform a systematic review evaluating the performance of various imaging studies for the detection of perineural spread, bony invasion, nodal metastasis (NM), and distant metastasis in cutaneous squamous cell carcinoma. Four databases were searched for relevant terms. Articles were included if they presented primary data on 5 or more subjects with cutaneous squamous cell carcinoma who underwent imaging to detect perineural spread, bony involvement, NM, or distant metastasis. Thirty studies and 1,027 subjects were included in the pooled analysis. Magnetic resonance imaging had a 94.9% sensitivity in detecting perineural spread. Computed tomography (CT) demonstrated a sensitivity of 75.7% and specificity of 98.6% in detecting bony invasion. While ultrasound, positron emission tomography-computed tomography, and CT all performed reasonably well in detecting NM, CT demonstrated the highest sensitivity (96.4%) and specificity (100%). Imaging changed management in up to 33% of cases. Imaging is useful in high-risk cutaneous squamous cell carcinoma. Magnetic resonance imaging performs best in the detection of perineural spread, and CT is the most accurate modality to detect bony invasion and NM.